Health Affliction and Medical Service of Tea Plantation Women Workers in Sri Lanka: An Anthropological Study Based on Alton Estate-2021 - Helanjanani, Shammuganathan (Future Science / FSH-PH Publications, 2022)
This research Studies “Health affliction and medical service of tea plantation women workers in Sri Lanka: An anthropological study based on Alton – 2021” This study focused on women workers in the tea plantation. This study problem highlights general health conditions of the women workers. The plantation management provides not quality of the medical specialties for the tea estate. Thereby most of the women workers are facing challenges to get proper medical services. Women workers more contributed for the economic sector in the Sri Lanka. Therefore the government should protect them. According to this study use primary and secondary data collection method, in short time; to selected sample size 12 from tea estate of Alton in Horana plantation. Women workers and health issues research relating women workers are suffering from fever, cough, cold, stomach pain, weakness, eye pain, headache, skin diseases, chest pain, asthma, breathing trouble, Hand pain , leg pain and Pregnancy. This study argues why they cannot get in correct way of the government medical service in the tea plantation. According to this issues, what are the problem are overcome. And provide good medical service and treatment for women worker in the tea plantation. Manage the situation to develop the hill country community. This is the way to research in this area. As well as I suggested some of the idea and commons in this problem. 12 samples were selected from a simple resource among the people belonging to 660 families living in study area and numerical and characteristic data on the conditions of the study area were read. This study concern research place situation to choice to use qualitative research method and used sample random sampling method to observed and read to get many idea and knowledge relevant the research problem to done this research. This research mainly focused what are different between nation and plantation medical service system. This research should be given the important for hill country community people. They are structurally different for other Sri Lankan community people. They are not receiving Sri Lanka welfare schemes in equally. According to this study provides a critical analysis and suggestions.